2014
DOI: 10.1080/20445911.2014.892494
|View full text |Cite
|
Sign up to set email alerts
|

How retellings shape younger and older adults' memories

Abstract: The way a story is retold influences the way it is later remembered; after retelling an event in a biased manner people subsequently remember the event in line with their distorted retelling. This study tested the hypothesis that this should be especially true for older adults. To test this, older and younger adults retold a story to be entertaining, to be accurate, or did not complete an initial retelling. Later, all participants recalled the story as accurately as possible. On this final test younger adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“… Davis et al (2015) have shown in a study on gist and detail that older populations (above 60) focus on gist. This could explain why the slightly shorter stories by older retellers in our studies preserved surprise affects at the same rate as younger retellers, since surprise is tied to the basic event and thereby likely to be captured as gist (for age differences in retellers, see also Barber and Mather, 2014 ; for narrative complexity in children, see Kulkofsky et al, 2008 ).…”
Section: Resultsmentioning
confidence: 71%
“… Davis et al (2015) have shown in a study on gist and detail that older populations (above 60) focus on gist. This could explain why the slightly shorter stories by older retellers in our studies preserved surprise affects at the same rate as younger retellers, since surprise is tied to the basic event and thereby likely to be captured as gist (for age differences in retellers, see also Barber and Mather, 2014 ; for narrative complexity in children, see Kulkofsky et al, 2008 ).…”
Section: Resultsmentioning
confidence: 71%
“…If the purpose of the story is to entertain the listener or facilitate social bonding, slight embellishments or the inclusion of inaccurate supplemental information may serve to enhance the story quality. Research from Barber and Mather [ 23 ] support this idea. In this study, they found that when older adults were explicitly told to focus on accuracy when initially retelling stories, they later recalled information from the story more accurately than older adults who initially retold the story for the purpose of being entertaining.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in some situations, a conversation regarding an event that happened in the world may be geared toward entertaining the current listener. At other times, telling of the story focuses on the symbolic, deeper meaning, take-home moral of the event, or how it coheres with the larger story [ 14 , 23 ]. In such cases, accuracy of literal details of the event may be less of a priority.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One generative goal involves passing along knowledge. Older adults tell better stories than young adults, focusing on gist over details (Barber & Mather, 2014) and tuning to their audience; for example, they simplify stories and elaborate more when a child, rather than an experimenter, is listening. Online, older adults may overlook errors to share a moral message (e.g., about a political candidate or party) with young followers.…”
Section: Social Changesmentioning
confidence: 99%